The role of tacit knowledge in the formation and continuation of architectural patterns case study: garden-houses of Meybud, Iran - Danaeinia, Ahmad; Hodaei, Masoud (Journal of Architecture and Urbanism, 2019)
Human has a dimension of knowledge named the tacit knowledge that the main important part of it is obtained through experience and direct connection with phenomena over time that turns into a pattern. Based on knowledge and intelligent use of it, the garden-house pattern appears to have an unbreakable bond with the nature and the understanding of both social and cultural rules of users. The research questions at first place discuss the role of tacit knowledge in shaping the architecture of garden-houses of Meybud and how this knowledge has appeared in architecture of garden-houses of Meybud. Qualitative research method and data collection method relies on library studies and field research. The results indicate that the patterns of housing in Meybud have shaped based on the recognition of two components of environment (the climate and natural context) and human (social norms), understanding of these two and applying them. The tacit knowledge and reliance on experiences is very influential and the garden-house pattern is institutionalized as the most sustainable pattern of architecture.